ARTIFICIAL INTELLIGENCE IN ENVIRONMENTAL MONITORING AND CONSERVATION - Rautela, Kamakshi; Kumawat, Kalpana; Rahman, Fardeen; Om Patidar, Hari (International Journal of Psychosocial Rehabilitation, 2020)
This paper presents and explores how to improve environmental sustainability with the help of artificial intelligence (AI). This study evaluates the potential environmental benefits of AI adoption, such as reductions in climate change, agriculture, ocean health, water resources, weather forecasting, and disaster resiliency. Upon conducting a thorough analysis of the available literature, it was found that there is a research deficiency in the utilization of artificial intelligence and decision support systems, as well as optimization models. This study employs qualitative analysis to explore sustainable uses of AI and the environmental impact of AI. It emphasizes. the importance of promoting environmental sustainability through AI and proposes the “environmental sustainability. by AI" approach as a prerequisite for developing transparent, responsible, and human-centered AI systems. The study primarily focuses on identifying ways in which AI can be utilized for sustainable environmental practices, with a particular emphasis on the role of AI in promoting environmental sustainability. This study has some limitations, one of which is its limited scope. The paper does not provide an extensive analysis of global environmental policies, which could potentially identify areas for cooperation or common ground. Additionally, the study’s focus on environmental sustainability means that it neglects the economic and social aspects of sustainability, which could be further explored. The study can aid stakeholders in comprehending global efforts to enhance environmental sustainability through the implementation of AI.